CONCEPT AND FUNCTION OF HUMAN RESOURCE MANAGEMENT IN ORGANIZATIONS - Rahmalinda, Rahmalinda; Anissa, Kholifah; Umam, Khoirul; Pangestu, Prasetyo Aji; Saputra, Handika; Hadiati, Eti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Human Resources (HR) is a crucial element in achieving organizational goals. Effective Human Resource management impacts various operational aspects of an organization, including efficiency, productivity, and competitiveness. This article explores the basic concept of Human Resources, delves into its strategic functions, and examines how Human Resources contribute to organizational success across various industry sectors. In Human Resource management, there are numerous aspects that HR managers must consider, including the basic concept of Human Resources itself, as well as the functions involved in HR management. The concept of Human Resources encompasses the fundamental understanding of human beings as valuable assets that can be utilized to achieve organizational goals.In this study, the author employs a descriptive qualitative approach to collect secondary data from various literature and research related to Human Resource management. The findings indicate that Human Resources play a critical role in supporting innovation, employee development, and strategic planning within organizations. Additionally, HR functions such as recruitment, selection, training, development, and performance evaluation are vital in ensuring that employees can contribute optimally to organizational objectives. The results of this article are expected to provide deeper insights for both practitioners and academics on how to leverage Human Resources to achieve organizational success.